2014
DOI: 10.1002/hup.2445
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in bipolar disorders during hospitalization and at discharge predicts clinical and psychosocial functioning at follow‐up

Abstract: Having been prescribed anxiolytics and atypical antipsychotics during hospitalization predicted reduced psychosocial functioning, whereas prescription of lithium at discharge was associated with better psychosocial functioning at follow-up. Future studies are needed in order to investigate how psychosocial functioning may be related in the long-term to pharmacological treatment in patients after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…Although hospitalization rate provides only a coarse marker of clinical outcome, it is highly relevant in terms not only of healthcare costs and service planning, but also of disruption of the life of an individual and their significant others; in fact, over one in four individuals in this population were hospitalized over one year of follow‐up (Table ). It is possible that measuring other, more fine‐grained measures, such as clinical and functional status, would tell a different story, although the only study to do so also found better outcome in those treated with lithium …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although hospitalization rate provides only a coarse marker of clinical outcome, it is highly relevant in terms not only of healthcare costs and service planning, but also of disruption of the life of an individual and their significant others; in fact, over one in four individuals in this population were hospitalized over one year of follow‐up (Table ). It is possible that measuring other, more fine‐grained measures, such as clinical and functional status, would tell a different story, although the only study to do so also found better outcome in those treated with lithium …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that measuring other, more fine-grained measures, such as clinical and functional status, would tell a different story, although the only study to do so also found better outcome in those treated with lithium. 23 Combination therapy was associated with a higher probability of hospitalization but longer retention on treatment. While indices of severity and complexity did not differ substantively among monotherapy groups, except for the expectable differences in the rate of psychosis, the combination groups may have represented a more complex or severely ill population ( initiators may be more susceptible to intention bias than comparisons among monotherapies, and conclusions must be drawn carefully.…”
Section: Main Findings In Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Uno studio compiuto presso il nostro reparto su 85 pazienti affetti da disturbo bipolare e seguiti in media per 31 mesi, ha rilevato che i pazienti ai quali era prescritto il litio alle dimissioni presentavano un migliore funzionamento psicosociale al follow-up rispetto a pazienti assegnati ad altre terapie come antipsicotici atipici e anticonvulsivanti. Questo dimostra che la terapia con litio restituisce una buona qualità di vita, favorendo attività psicosociali importanti per la quotidianità dei pazienti [24].…”
Section: Discussioneunclassified